Treating Patients With Locally Advanced Squamous Cell Carcinoma of the Head and Neck Unsuitable to Receive Cisplatin-Based Therapy - Porceddu, Sandro V.; Scotté, Florian; Aapro, Matti; Salmio, Satu; Castro, Ana; Launay-Vacher, Vincent; Licitra, Lisa (Frontiers in Oncology, 2020)
Concurrent chemoradiotherapy with high-dose cisplatin (100 mg/m2 every 3 weeks) is the preferred regimen with curative intent for patients with unresected locally advanced squamous cell carcinoma of the head and neck (LA SCCHN). This treatment is associated with acute and late toxicities, including myelosuppression, severe nausea/vomiting, irreversible renal failure, hearing loss, and neurotoxicity. Because of cisplatin’s safety profile, treatment adherence to high-dose cisplatin can be suboptimal. Patients commonly receive less than the total cumulative target dose of 300 mg/m2 or the minimum recommended dose of 200 mg/m2, which can have a negative impact on locoregional control and survival. Alternatively, cetuximab plus radiotherapy may be most suitable for patients at high risk of nonadherence to high-dose cisplatin. We discuss the baseline characteristics dictating the unsuitability/borderline unsuitability of cisplatin and the available alternative evidence-based treatment regimens for patients with LA SCCHN. We nonsystematically reviewed published phase II and III trials and retrospective analyses of high-dose cisplatin-based chemoradiation in LA SCCHN conducted between 1987 and 2018, focusing on recent key phase III studies. We defined the baseline characteristics and associated prescreening tests to determine unsuitability and borderline unsuitability for high-dose cisplatin in combination with radiotherapy in patients with LA SCCHN. Patients with any preexisting comorbidities that may be exacerbated by high-dose cisplatin treatment can be redirected to a non–cisplatin-based option to minimize the risk of treatment nonadherence. High-dose cisplatin plus radiotherapy remains the preferred treatment for fit patients with unresected LA SCCHN; patients who are unsuitable or borderline unsuitable for high-dose cisplatin could be identified using available tests for potential comorbidities and should be offered alternative treatments, such as cetuximab plus radiotherapy.